EXPERIMENT AND NUMERICAL STUDY ON TEMPERATURE DISTRIBUTION OF AN AIR- COOLED CONDENSER SIMULATOR - SURYOPRATOMO (NIM : 13105072); Dosen Pembimbing Dr.Ir.Prihadi Setyo Darmanto, EDO
Sea wind entraining a couple of air-cooled chiller in a line damages the next chiller following the 1st chiller on the winds trajectory. Damage occured on the 2nd year of a total 15 year of normal chiller operation. Arrangement of chillers perpendicular to the winds direction seems to be a solution to the problem. This solution can be proven by viewing the air temperature disribution along the condenser. Temperature distribution of the air can be viewed by an experiment involving a model of the condenser and utilizing a CFD numerical simulation. The model of condensor is geometrically scaled by 1:100. Experiment is conducted by variating the wind speed and direction and the spacing between condensers. Experiment and CFD both shows a similar result. Results shows a good chosen ratio of distance between fan centreÃ‚Â’s and fan diameter for condensers in a line and perpendicular with sea wind, respectively, is achieved at a minimum of 9 dan 3,8. At a city impeded by sea wind, where a number of air-cooled condensers are needed, the arrangement of condensers should be perpendicular with the wind trajectory. In addition, a ratio of distance between centres of fan and fan diameter should be held a minimum of 3,8.